Helical Magnetic Cavities: Kinetic Model and Comparison With MMS Observations - Jing‐Huan Li; Xu‐Zhi Zhou; Fan Yang; Anton V. Artemyev; Qiu‐Gang Zong (Geophysical Research Letters)
Abstract Magnetic cavities are sudden depressions of magnetic field strength widely observed in the space plasma environments, which are often accompanied by plasma density and pressure enhancement. To describe these cavities, self‐consistent kinetic models have been proposed as equilibrium solutions to the Vlasov‐Maxwell equations. However, observations from the Magnetospheric Multi‐Scale (MMS) constellation have shown the existence of helical magnetic cavities characterized by the presence of azimuthal magnetic field, which could not be reconstructed by the aforementioned models. Here, we take into account another invariant of motion, the canonical axial momentum, to construct the particle distributions and accordingly modify the equilibrium model. The reconstructed magnetic cavity shows excellent agreement with the MMS1 observations not only in the electromagnetic field and plasma moment profiles but also in electron pitch‐angle distributions. With the same set of parameters, the model also predicts signatures of the neighboring MMS3 spacecraft, matching its observations satisfactorily.